(untitled) (The Review of Diabetic Studies, 2023)
The aim of this pilot study was to compare the effects of an intensive nutritional intervention with usual care conditions on dropout rate, body weight, lifestyle changes and glycemic control in patients with type 2 diabetes mellitus (T2DM). Thirty outpatients with T2DM but without insulin treatment (mean age: 57 ± 9 yr) were randomly assigned to one of the two intervention groups: intensive care (IC) or usual care (UC). Patients in the UC group were given advice about dietary and physical activity goals in one consultation session at baseline, while patients in the IC group attended five goaloriented consultation sessions held approximately every two weeks from baseline onwards. Changes in body weight, T2DM knowledge, dietary intake, physical activity, HbA1c, and percentage of dropouts were evaluated at 1-year followup post-intervention. Fifty percent of patients quitted the program and were classified as “dropouts”. Program completers were older and included a lower percentage of newly diagnosed T2DM compared with dropouts. A tendency to a negative association between attendance of the IC group and the likelihood of dropping out was found (p = 0.08). No difference was detected between UC and IC groups regarding changes in body weight, HbA1c or other outcome measures, at post-intervention or 1-year follow-up. This pilot study did not confirm advantages of intensive nutritional intervention in T2DM patients in terms of glycemic control, body weight, diet and physical activity. However, the high dropout rate may have hampered its effectiveness.